The Impact of Isolated Versus Multiple Osteochondromas: Analysis of the CoULD Registry. Issue 7 (24th August 2022) - Wessel, Lauren E.; Goldfarb, Charles A.; Vuillermin, Carley; Hutchinson, Douglas T.; Bohn, Deborah; Steinman, Suzanne; Wall, Lindley B.; ,
Abstract : Purpose: The burden of upper extremity (UE) osteochondromas on function and self-perception among pediatric patients is unclear. The purpose of our study was to study the impact of osteochondromas in comparison to population norms and to evaluate solitary versus multiple osteochondromas on subjective UE function as measured by patient rated outcomes. Methods: We utilized the CoULD (Congenital Upper Limb Differences) Registry to review all pediatric patients presenting with osteochondromas between January 2014 and February 2021. Demographic information was collected and patients were classified as having either single or multiple osteochondromas. Patient-Reported Outcome Measurement Information System (PROMIS) and Pediatric Outcomes Data Collection Instrument (PODCI) tools were utilized for assessment. Scores for PODCI subscales of UE function, Pain/comfort, and Happiness and PROMIS domains of UE Function, Pain, Depression, Anxiety, and Peer Relations were reviewed. Differences between groups were analyzed using the Student t test. Results: Ninety-nine patients met inclusion criteria for the study with an average age of presentation of 9.3 years and 61 patients (62%) were male. Overall, patients demonstrated worse UE Function as well as greater Anxiety and Depression in comparison to the population normals on PROMIS assessment. Patients also demonstrated worse patient and parent reported PODCI UE, Sports and Physical Functioning, Pain/Comfort and Global Functioning scores compared with population norms but demonstrated better than average happiness scores. Patients with multiple osteochondromas demonstrated greater PROMIS pain interference and more disability in PODCI Sports and Physical Functioning, Pain/Comfort and Global Functioning compared with those with solitary osteochondromas. Conclusion: Patients with UE osteochondromas have worse overall function in comparison to population norms, exceeding established minimally clinically important difference values. In addition, patients with multiple osteochondromas reported more pain and poorer physical function than those with solitary osteochondromas. Physicians should be alert to the physical and psychosocial burden of this disease. Level of Evidence: Level II—prognostic.